Estimation of quality of life in patients, suffering cardiomyopathy of ischemic genesis, depending on the method of treatment - A. V. Gabriyelyan; S. V. Romanova (Клінічна хірургія, 2019)
Objective. To estimate the changes of the patients’ quality of life in those, suffering ischemic cardiomyopathy after surgical revascularization and transplantation of the stem cells, obtained from umbilical blood.